Borderline paratubal cyst: a case report - Alaoui, Fatima Zohra Fdili (The African Field Epidemiology Network, 2012)
Borderline para-ovarian cysts (PCs) are rare entities. They are commonly present in the third decade. Borderline PCs are often discovered fortuitously on routine ultrasound examination or they are common incidental findings during a laparotomy. They must be differentiated from simple ovarian cysts, peritoneal inclusion cysts and hydrosalpinges on ultrasound sonography. Papillary projections on the cyst wall should be searched carefully to suggest diagnosis. The treatment is surgical including fertility -sparing operation or more radical surgery depending on the case. The prognosis is good because borderline PCs are usually early-stage at diagnosis. Here is a report of a 38- year old woman with a borderline paratubal cyst. Adnexal torsion of hydrosalpinx was suspected; thus, she underwent an urgent surgery. Cystectomy was performed without rupture. The final diagnosis revealed a borderline PC. The patient underwent a radical surgery. Currently, she has had no evidence of disease recurrence.